THE POLITICS OF REPRESENTATION AND FEMALE LEADERSHIP IN GANGUBAI KATHIAWADI: A ROLAND BARTHES SEMIOTIC ANALYSIS - Siti Nurul Hidayah; Muhammad Akbar; M. Iqbal Sultan (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study examines the representation of female leadership in film Gangubai Kathiawadi and its role in challenging patriarchal ideology within the Indian socio-cultural context. Employing a qualitative interpretive method, this reseach applies Roland Barthes’s semiotic analysis to explore denotative, connotative, and mythical meanings embedded in key scenes depicting the protagonist’s transformation from a marginalized woman into a community leader. The findings reveal that female leadership is constructeed through a system of visual and narrative signs, including white attire, assertive bodily gesture, control of public space, empathetic interpersonal relations, and engagement with male-dominated power structures. At the connotative level, these signs signify moral legitimacy, courage, and social authority beyond formal institutional power or elite status. At the mythical level, the film produces an alternative narrative of leadership rooted in solidarity, care, and collective resistance emerging from marginalized social groups. The study concludes that Gangubai Kathiawadi operates as a cultural text that deconstructs patriarchal myths and redefines female leadership as a legitimate and transformative force in contemporary social and political discource.